Plan de marketing para el “centro comercial Quevedo Shopping Center” en el año 2015 - Barcia Cedeño, Jéssica M. (2015)
This thesis was performed at the "Quevedo Mall Shopping Center" located in Quevedo canton, Los Ríos province, in order to create a marketing plan from Quevedo Shopping Center Mall 2015. The work is included in the characteristics of the financial market and its need for greater segmentation and product differentiation offered, considering the sensitivity level of customer loyalty, changes in styles of consumption and financial competitive innovation. The first item of the financial market specialist literature was analyzed. And then proceeded to conduct a study that allowed us to know the positioning and public interest in this mall, although the majority of potential customers like modernity Mall and feel satisfied with the service provided; there is a percentage who are dissatisfied with the comfort that sold in the Mall. Subsequently, this allowed us to identify and analyze the skills and characteristics of each local participating in Quevedo Shopping Center. Finally, to have the necessary information, the Marketing Plan from "Quevedo Mall Shopping Center", which provides marketing strategies aimed at developing the positioning of this mall was performed. This plan further benefit the brand image Quevedo, which is a commercial area that is constantly growing and offers future opportunities from Quevedo city and its inhabitants.